HackaBIP: Possibilities and challenges of co-producing civic tech in Lisbon's local development - Farias, A. C. C. (CIDADES, Comunidades e Territórios, 2025)
This study explores the potential of civic hacking to enhance local development in Lisbon, focusing on the hackaBIP civic hackathon as a participatory model for the co-production of digital tools. The research asks how to engage local initiative organisations in civic tech co-production and adopts the civic hackathon as a collaborative methodology and as a basis for designing an information infrastructure for sustainable collaboration. The Lisbon Local Development Strategy BIP/ZIP served as the context, given the need to improve the collaboration and monitoring capacities of its network of actors, understood under the penta-helix model of social innovation. The results show that, despite the potential of the civic techs generated to explore available open data and generate other necessary data, the initiative faced significant challenges, such as power imbalances between community actors and tech developers. Discussions highlight the importance of the igniter actor in sustaining ongoing collaboration, the need for academic institutions to engage more actively with community initiatives, and the need for local governments to be more responsive. Ultimately, this research argues for the establishment of hackable universities - open and transdisciplinary academic environments that foster dialogue with local initiatives to increase civic engagement and contribute to building hackable cities.